From “Brushwork Centricity” to “Formative Reconstruction”: On the Paradigm Shift in Formal Expression within Ink Figure Painting - Li, Na; Tsetsegdelger D (International Journal of Social Sciences and Public Administration, 2025)
Since the 20th century, Chinese ink figure painting has undergone a profound modern transformation, its core manifestation being a paradigm shift from traditional “brushwork-centricism” towards “formative reconstruction” that integrates Western realist modelling. This paper aims to systematically trace the historical trajectory, intrinsic motivations, and concrete manifestations of this shift from the perspective of formal language within artistic ontology. It first delineates the independent aesthetic value of ‘brushwork and ink’ within the traditional literati painting system and its limitations in the realm of figure painting; Secondly, it focuses on analysing how the ‘Xu-Jiang System’ integrated sketching techniques into ink wash painting, laying the foundation for the new paradigm. Finally, by examining the practices of contemporary artists such as Zhou Jingxin and Liu Guohui, it explores how they creatively resolved the tension between brushwork and form, ultimately forging a novel formal language system that harmonises national connotations with modern visual tension.